2013
DOI: 10.1371/journal.pgen.1003906
|View full text |Cite
|
Sign up to set email alerts
|

Decoding a Signature-Based Model of Transcription Cofactor Recruitment Dictated by Cardinal Cis-Regulatory Elements in Proximal Promoter Regions

Abstract: Genome-wide maps of DNase I hypersensitive sites (DHSs) reveal that most human promoters contain perpetually active cis-regulatory elements between −150 bp and +50 bp (−150/+50 bp) relative to the transcription start site (TSS). Transcription factors (TFs) recruit cofactors (chromatin remodelers, histone/protein-modifying enzymes, and scaffold proteins) to these elements in order to organize the local chromatin structure and coordinate the balance of post-translational modifications nearby, contributing to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 96 publications
2
40
0
Order By: Relevance
“…Overall, NFY and NFY-like motifs, which are known cardinal elements of promoter regions 48 , have a much stronger influence on proximal binding sites, but very little influence on distal sites.…”
Section: Grad-cam Scores Give Insight Into Features Of Tf Bindingmentioning
confidence: 97%
“…Overall, NFY and NFY-like motifs, which are known cardinal elements of promoter regions 48 , have a much stronger influence on proximal binding sites, but very little influence on distal sites.…”
Section: Grad-cam Scores Give Insight Into Features Of Tf Bindingmentioning
confidence: 97%
“…The 70.1% of clusters mapping within 100bp of transcriptional start sites were highly enriched for GFY-Staf, Sp1, and Elk/ETS binding motifs, which are known promoter binding transcription factors. 27 Clusters mapping into other gene regions showed minimal enrichment of these motifs ( Figure 1B). To provide additional support for the promoter-enriched sequence clusters, ATAC sequencing and H3K4me3 ChIP-seq datasets were compared; Supplemental Table 2 Only 44.5% of bidirectional clusters mapped ±100bp within transcriptional start sites.…”
Section: Cage Sequence Clusters Identify Promoters and Enhancers Of Tmentioning
confidence: 99%
“…NF-Y is a trimeric protein formed by NF-Y subunit alpha (NF-YA), NF-Y subunit beta, and NF-Y subunit gamma, and exhibits sequence-specific binding to CCAAT boxes (Maity and de Crombrugghe, 1998). A genome-wide study indicated that CCAAT boxes are mainly located within a conserved distance of 2150 to 150 base pairs (bp) from the transcription start sites in 18% of the 21,000 human promoters (Benner et al, 2013). Structural analysis revealed that NF-Y bound DNA in a histone-like mode (Ceribelli et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Coimmunoprecipitation suggested the direct interaction between Sp1 and NF-Y in human cells (Roder et al, 1999;Lim and Chang, 2009). In the human genome, CCAAT and GC boxes are observed to have a high tendency to co-occur in regions 2150/150 bp from transcription start sites (Benner et al, 2013). In addition, NF-Y has genome-wide partnerships with Sp1, and the distances between the cis-acting elements are conversed (Dolfini et al, 2016).…”
Section: Introductionmentioning
confidence: 99%